Diagnosis of Atypical Chest Pain Using Ultrasound. (March 2016) - Olivieri, Patrick; Berkowitz, Rachel; Eaglstein, Emily; Rose, Gabriel; Siadecki, Sebastian; Saul, Turandot
While the common organs assessed in chest pain are the heart, lungs, and inferior vena cava, one must also consider other diagnoses. Splenic rupture can be either traumatic or atraumatic, and splenomegaly can make this vulnerable organ even more susceptible to injury. A case is reported of a patient who presented to the emergency department with a complaint of left-sided chest pain; a focused assessment with sonography for trauma (FAST) examination showed significant intraperitoneal free fluid consistent with splenic injury. The role of bedside sonography in acquiring a rapid and accurate diagnosis is discussed.